Future of Food : Harnessing Digital Technologies to Improve Food System Outcomes - World Bank Group (World Bank, Washington, DC, 2019)
Digital technologies have significant potential to improve efficiency, equity, and environmental sustainability in the food system. A range of digital technologies are already leading to: better informed and engaged consumers and producers, smarter farms, and improved public services. Adoption of digital technologies varies significantly across countries, with lower current adoption rates in low-income countries. Increasing adoption will require addressing supply-side factors, such as rural network coverage and availability of digital applications, and demand-side factors, including skills and knowledge, trust, affordability, and complementary investments. While digital technologies have significant potential they also pose several risks that need to be addressed including: an overconcentration of service provider market power; lack of data privacy; exclusion; and cybersecurity breaches. These risks cut across all segments of the economy, including the food system. In addition, digital technologies should not be viewed as a panacea. Other investments are needed to address the multiple constraints farmers face and to realize the potential benefits of digital technologies.